2016
DOI: 10.1002/jbt.21870
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative damage of the male reproductive system induced by paraquat

Abstract: The effects of paraquat (PQ) on the male reproductive system are unclear. In this study, male rats were divided into four groups (0, 0.5, 2, and 8 mg/kg) and treated with PQ by oral gavage for 8 weeks. At the end of the experiment, a significant decline in sperm count, motility, and viability and an increase in teratospermia were observed in the PQ-treated group (P < 0.05). Further investigation found that PQ resulted in enhanced lipid peroxidation and more apoptosis in the testis tissues, and apoptosis was li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Moreover, exposure to diquat corrodes the skin and gastrointestinal tract [ 26 ] and damages the kidneys, liver, heart, and central nervous system [ 25 ]. Meanwhile, paraquat, another dipyridyl herbicide, can induce deleterious changes in mammalian testis [ 27 , 28 , 29 , 30 ]. However, diquat is reportedly less potent in male reproductive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, exposure to diquat corrodes the skin and gastrointestinal tract [ 26 ] and damages the kidneys, liver, heart, and central nervous system [ 25 ]. Meanwhile, paraquat, another dipyridyl herbicide, can induce deleterious changes in mammalian testis [ 27 , 28 , 29 , 30 ]. However, diquat is reportedly less potent in male reproductive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Direct mechanisms include mitochondrial and extramitochondrial production of oxygen radicals, whereas impact on the antioxidant defense system is considered an indirect mechanism . Notably, chemical induction of oxidative stress is not restricted to carcinogens nor carcinogenesis. …”
Section: Chemical Induction Of Oxidative Stressmentioning
confidence: 99%
“…Various exogenous chemicals may affect sperm production and maturation in testes [ 13 ]. PQ suppresses the endogenous anti-oxidant enzymes and generates free radicals [ 14 ]. These free radicals stimulate the ROS production in the testicular tissues, which eventually prompts oxidative stress (OS) that can impair the Leydig and Sertoli cells [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, PQ exposure instigates sperm mitochondrial damage that eventually reduces the formation of ATP necessary for sperm motility [ 17 ]. Previous literature has reported that PQ intoxication loweres hormonal levels (FSH, LH and testosterone) and anti-oxidant activities [ 14 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%